Linguistic construction of ethnocultural identity of Mandarin-speaking and English-speaking urban Chinese in Peninsular Malaysia - Shik, Pei Yen (2015)
The population in Malaysia consists of various races and hence there is a significant need of looking into the language and identity of different races. This study mainly focuses on ethnic Chinese. Historically, Chinese in Malaysia originated from China and they could only speak their own mother tongue, and have their own tradition. However, this phenomenon has changed due to various reasons. Chinese in Malaysia today may speak more foreign languages such as English and there is a high possibility that some of them do not even speak Mandarin at all. It is important to ascertain one’s ethnocultural identity as it is used to represent a person’s cultural background regarding their ethnic. Identity can also be referred to who a person ‘really is’ and how a person is characterized or represented. When identity is considered in the context of ethnocultural identity, it is mainly the identity of a person which is constructed through face to face interaction in their daily livings. Hence, the ethnocultural identity in this study has been sought out through participants’ linguistic construction. This study attempts to describe the language use of the Mandarin speaking and English speaking urban Chinese with the family, describe the language use of the participants with non-family members, compare the influence of socio-economic status on the language use of the participants with non-family members and lastly in to compare the cultural practice of the participants. Language choice among the ethnic Chinese in west Malaysia is very much influenced by the individual’s perception and interpretation of the label Chinese, which in turn determines their acceptance or rejection of it. On the basis of language choice, there are two subgroups of Chinese that can be noted: those who speak English in public and private domains; and those who speak Mandarin regularly.Orders of discourse by Norman Fairclough (1989; 1995; 2001) are an important approach in this study. There are three areas of analysis to find out the linguistic construction of ethnocultural identity among ethnic Chinese in west Malaysia, which are discourses, genres and styles. This study explores the differences of Mandarin speaking and English speaking Chinese from the aspect of linguistic construction. The sampling of this study is a convenience sampling. The survey covers about 300 participants (Chinese) which are randomly selected between aged 17 to 30 years old. They stay in urban area in Peninsular Malaysia. The statistical tests and significance of relationships or differences were being tested in this study. The results are then grouped and compared based on two language groups which are English speaking and Mandarin speaking group. Their language choice can be easily identified through interview and questionnaire, and hence the belonging to either group can be determined. Through this study, it can be concluded that the factors which influenced the ethnocultural identity are friends, parents and educational background. The factor of friend has the strongest influence on participants’ ethnocultural identity. Furthermore, the overlapping in their ethnocultural identity is inevitable as this study is done in Malaysia context. The result has shown that although the language choice for both speaking groups is different, they have similarities in ethnocultural identity. They present similarities in ritual activities and festivals. It is possible that participants’ cultural practices and their thinking may not match. From here, there is a strong justification that both groups exhibit association in Chinese and western culture in the way of their cultural practice.